Fixed Point Approximation of Monotone Nonexpansive Mappings in Hyperbolic Spaces. (10th August 2021) - Kalsoom, Amna; Saleem, Naeem; Işık, Hüseyin; Al-Shami, Tareq M.; Bibi, Amna; Khan, Hafsa
Abstract : Fixed points of monotone α -nonexpansive and generalized β -nonexpansive mappings have been approximated in Banach space. Our purpose is to approximate the fixed points for the above mappings in hyperbolic space. We prove the existence and convergence results using some iteration processes.